Nucleospora hippocampi n. sp., an Intranuclear Microsporidian Infecting the Seahorse Hippocampus erectus From China - Wang, Yuan; Ying, Na; Huang, Yanqing; Zou, Xiong; Liu, Xin; Li, Letian; Zhou, Junfang; Zhao, Shu; Ma, Rongrong; Li, Xincang; Tan, Hongxin; Fang, Wenhong (Frontiers in Cellular and Infection Microbiology, 2022)
The life cycle, ultrastructure, and molecular phylogeny of a new intranuclear microsporidian, Nucleospora hippocampi n. sp., infecting the intestine of Hippocampus erectus, were described. The histopathology revealed the extensive infection mainly in the columnar epithelium of the intestinal mucosa layer. The enterocytes were the important target cell for Nucleospora seahorse n. sp. infection. Transmission electron microscopy results showed that this microsporidian developed directly within the host cell nucleoplasm. In the intranuclear life cycle, the transformation from meront to sporogonial plasmodium was recognized by forming electron dense discs structures, which were considered as the polar tube precursors. The microsporidian showed the typical morphological characteristics of the family Enterocytozoonidae that the formation and development of spore organelles prior to the division of the sporogonial plasmodium. Eight spores were generally formed in a single host nucleus according to wet smears observation. Mature spores were elongate ovoid with slightly bent, and measured 1.93 × 0.97 μm. The isofilar polar tube was arranged in 7 8 coils in one row. Phylogenetic analysis of its small subunit ribosomal DNA sequences demonstrated the parasite belonged to the Nucleospora group clade. The histological, ultrastructural, and molecular data support the erection of a new species in the genus Nucleospora. This is the first report of Nucleospora species in Asia and threatened syngnathid fishes.